El Alamein and the struggle for North Africa international perspectives from the twenty-first century - Edwards, Jill (Jill Mary) (American University in Cairo Press, 2012)
From the ongoing Italian geomorphic study of the Alamein arena to individual memories of non-combatant Alexandrians, from the Free French to the seasoned colonial forces of Australia, India, New Zealand, and South Africa, and from vital naval engagements and the siege of Malta to the study of Rommel's leadership and the Churchill-Montgomery duo, this book offers a detailed yet broad reassessment of the complexities of the war in North Africa between 1941 and 1943, its technology, philosophy, military doctrine, strategy, tactics, logistics, and the associated local and international politics.